2004
DOI: 10.1128/jvi.78.22.12428-12437.2004
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of a Drug-Dependent Human Immunodeficiency Virus Type 1 Variant during Therapy with the T20 Fusion Inhibitor

Abstract: The fusion inhibitor T20 belongs to a new class of anti-human immunodeficiency virus type 1 (HIV-1) drugs designed to block entry of the virus into the host cell. However, the success of T20 has met with the inevitable emergence of drug-resistant HIV-1 variants. We describe an evolutionary pathway taken by HIV-1 to escape from the selective pressure of T20 in a treated patient. Besides the appearance of T20-resistant variants, we report for the first time the emergence of drug-dependent viruses with mutations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
183
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(196 citation statements)
references
References 42 publications
12
183
1
Order By: Relevance
“…Refolding rates of these conformationally destabilized mutant F trimers are enhanced, resulting in a hyperfusogenic phenotype and, possibly, a narrowed window of opportunity for small-molecule docking and interference with F trimer rearrangements leading to fusion pore formation. Different escape pathways were also identified for HIV resistance to the peptidic entry inhibitor Fuzeon (52,53). However, Fuzeon escape did not coincide with resistance to other entry inhibitors (54).…”
Section: Discussionmentioning
confidence: 93%
“…Refolding rates of these conformationally destabilized mutant F trimers are enhanced, resulting in a hyperfusogenic phenotype and, possibly, a narrowed window of opportunity for small-molecule docking and interference with F trimer rearrangements leading to fusion pore formation. Different escape pathways were also identified for HIV resistance to the peptidic entry inhibitor Fuzeon (52,53). However, Fuzeon escape did not coincide with resistance to other entry inhibitors (54).…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, results showed that N28Fd was much more resistant to proteinase digestion than T20, prolonging the existence of N28Fd in the human circulatory system. Finally, N36Fd and N28Fd potently inhibit a series of T20-resistant strains, although we cannot exclude the possibility that these NHR trimers may loose antiviral activity against the HIV-1 variants with compensatory mutations in the CHR region (42)(43)(44). Because N28Fd and T20 target different regions of gp41, combining them in clinical practice should help to avoid generating viruses otherwise resistant to either one alone.…”
Section: Discussionmentioning
confidence: 99%
“…The membrane-anchored C-peptide binds to the free version of gp41 N peptides, suggesting that the membraneanchored C peptides exert their biological effect by binding gp41. 54 Although the appearance of resistant variants might be inevitable, 55 entry inhibitors as those that interfere with fusion carry great hope for anti-HIV therapy.…”
Section: Intrabodies Against Viral or Viral-related Host Proteins Canmentioning
confidence: 99%